2020
DOI: 10.21273/hortsci15255-20
|View full text |Cite
|
Sign up to set email alerts
|

‘Ray Ruby’ Grapefruit Affected by Huanglongbing II. Planting Density, Soil, and Foliar Nutrient Management

Abstract: Since the arrival of Huanglongbing (HLB) disease in Florida, several management approaches, including modification of orchard architecture design and nutritional therapy, have been explored. High-density plantings anticipate early economic returns from HLB-affected orchards. With no cure available for HLB, balanced nutrient application through soil and foliar spraying can mitigate the disease. A 2-year study was conducted to investigate the effects of three grapefruit (Citrus paradisi) planting densities [sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The high planting density used in this study (1111 trees/ha) might have masked the effects of plant nutrition on vegetative growth variables, as higher densities promote higher competition among nutrients, water, space, and light, which may affect vegetative growth (Weil and Brady, 2017). This is supported by the findings of Phuyal et al (2020aPhuyal et al ( , 2020b who observed lower canopy volume and trunk diameter with a high planting density (975 trees/ha) when compared with lower planting densities of (300 and 440 trees/ha) of 'Ray Ruby' grapefruit on Kuharske citrange. However, they found greater fruit yield per hectare with the highest planting density, with no significant yield difference among fertilizer treatments.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The high planting density used in this study (1111 trees/ha) might have masked the effects of plant nutrition on vegetative growth variables, as higher densities promote higher competition among nutrients, water, space, and light, which may affect vegetative growth (Weil and Brady, 2017). This is supported by the findings of Phuyal et al (2020aPhuyal et al ( , 2020b who observed lower canopy volume and trunk diameter with a high planting density (975 trees/ha) when compared with lower planting densities of (300 and 440 trees/ha) of 'Ray Ruby' grapefruit on Kuharske citrange. However, they found greater fruit yield per hectare with the highest planting density, with no significant yield difference among fertilizer treatments.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast, Atta (2019) did find that the 280 kgÁha À1 N rate significantly increased canopy volume of 'Hamlin' on Swingle rootstock, indicating that scion and rootstock selections can affect fertilization experiments of HLB-affected trees. Similarly, Phuyal et al (2020aPhuyal et al ( , 2020b found that higher N, Mg, and micronutrient inputs increased canopy volume of 'Ray Ruby' grapefruit on Kuharske citrange, although this occurred at the expense of fruit yield.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[26]. However, a study by Phuyal et al [27] found that supplemental soil and foliar micronutrient applications with 0, 1.5×, 3×, and 6× the recommended UF/IFAS rates of B, Mn, Fe, and Zn did not improve yield or tree growth of HLB-affected 'Ray Ruby' grapefruit trees on 'Kuharske' rootstock in the IRD. Another study found that ground fertilizer applications of B with 0, 2×, and 4× the current UF/IFAS recommendation of B had no consistent impact on tree canopy for 9-year-old 'Vernia' sweet orange trees on Rough Lemon rootstock [28].…”
Section: Introductionmentioning
confidence: 94%
“…For several years, it has been reported that the application of enhanced nutritional products can extend the vigor of HLB-affected citrus and trigger citrus defense against C Las ( Spann and Schumann, 2009 ; Shen et al, 2013 ; da Silva et al, 2020 ; Shahzad et al, 2020 ; Dong et al, 2021 ). Although nutrient treatments have no effect on reducing C Las titer and cannot enhance yield of HLB-affected citrus in the field ( Gottwald et al, 2012 ; da Silva et al, 2020 ; Phuyal et al, 2020 ), the application of macro-and micronutrients have been adopted worldwide as they induce host defenses and help maintain production of HLB-affected trees. For instance, a field study in Florida showed application of phosphorus (P) oxyanion solutions to HLB-affected citrus mitigated disease symptom severity during a 3-year field trial ( Zhao et al, 2013 ).…”
Section: Host Defense Triggered By Agentsmentioning
confidence: 99%